STRATEGI GURU AKIDAH AKHLAK DALAM PEMBENTUKAN AKHLAK SISWA KELAS VIII DI MTs AL-FURQON KABUPATEN KARAWANG - Faujiah, Sifa; Akil, Akil; Nurlaeli, Acep (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Morals are one measure of a person's high and low degrees, so in describing one of the first steps in educating true morals is to instill Islamic religious education into children as early as possible. This study discusses the application of the teacher's learning strategy on the moral principles in the moral formation of class VIII students at MTs Al-Furqon, Karawang Regency. The purpose of this research is to find out the teacher's strategies for moral belief, student morals, supporting and inhibiting factors in the formation of morals. To get answers and solutions to the problems above, the authors conducted qualitative research. After analyzing the data obtained, the results show an increase in the morals of class VIII students at MTs Al-Furqon, Karawang Regency. Through the application of direct, inquiry and cooperative learning strategies. The process of implementing the learning strategy is generally carried out through three stages, namely the initial stage, teaching and assessment. The conclusion in this study is that the various processes of applying the teacher's learning strategies for the moral principles in the moral formation of class VIII students at MTs Al-Furqon, Karawang Regency, must still be applied. The formation of morals, is enhanced by various kinds of creativity that can support the moral development process. The maximum effort made by the teacher of aqidah morals in the formation of the morals of class VIII students at MTs Al-Furqon, Karawang Regency, requires innovation so that it further explores the potential of existing educational resources for sustainable development. Support for all aspects of education, preferably in line with the formation program carried out by the teacher of morals, especially in exemplary, habituation and supervision in the family, community and school environment